Pengaruh Sistem Informasi Akuntansi Dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah - Bale, Priscilla Julitha; Marlina, Tri; Muanas, Muanas; Fahmie, Arief (Jurnal Informatika Kesatuan, 2023)
Financial reports are considered qualified if they are relevant, comparable, understandable and reliable. With the existence of an accounting information system, of course it will help effectiveness, relevance, efficiency and can make a report accurate. An accounting information system that does not use an internal control system is likely to have little benefit. The purpose of establishing an internal control system is to provide reliable and reliable financial reports. This study aims to examine the effect of accounting information systems and internal control systems on the quality of local government financial reports. The population in this study is the local government of Kupang City. The sample for this study used a non-probability sampling technique obtained from the finance department at 23 official offices in Kupang City. There are 69 respondents in this study. Data was collected by distributing questionnaires directly to 23 offices in Kupang City. The data analysis technique used is multiple regression analysis, partial test (t), and simultaneous test (f) using SPSS 29. The results of this study state that the Accounting Information System has no effect on the Quality of Financial Statements, the Internal Control System has an effect on the Quality of the Financial Reports of the Regional Government of Kupang CityKeywords: Accounting Information System, Internal Control System, Report Quality, Quality of the Financial Reports of the Regional Government of Kupang City